Double Consciousness: A Subject Formation in Toni Morrison’s Tar Baby - Neupane, Khagendra (Journal of Population and Development, 2024)
This paper based on Toni Morrison's "Tar Baby" delves into the intricacies of race, identity, and belonging. It explores the expressions of double consciousness in Morrison's work and its significance in understanding the characters' motivations and relationships. It employs W.E.B. Du Bois’s concept of double consciousness as a literary tool to describe the internal conflict experienced by African Americans. Double consciousness refers to the psychological experience of African Americans who perceive themselves both as individuals and as members of a racially marginalized group. This duality arises from the social construction of race and the historical context of oppression, leading to a fragmented identity. The female protagonist, Jadine Childs, embodies the struggle of double consciousness as a young, educated black woman. She gets divided between her African heritage and the allure of white culture. Her relationship with Son, a male protagonist, serves as a catalyst for her exploration of self-awareness and cultural identity. This study examines how Morrison portrays the internal conflicts faced by her characters. Additionally, it navigates the reasons behind the formation of split personality of the characters. It also discovers the role of history and memory in shaping the characters' perceptions. Over all, this research contributes the readers to comprehend how double consciousness acts in order to formulate fragmented personality of the black characters.